Problematizing traditional criminological perspectives on thugs and gangs - Marques, Olga (Thug criminology, 2023)
Gangs are a survival unit that happens in the neighbourhood because people are tough. Young men decide: If we clique up, we’re safer. That’s all a gang starts out being. A protection unit. Then we decide, if three of us are tough, five of us are tougher. Meanwhile none of us has anything. Take the gangbangers’ outfit. It is the least expensive clothing: A white tee shirt, some Converses, pressed jeans, a carefully folded rag. That’s not by choice. That’s the cheapest shit at the swap meet. So what the ghetto kids have done is take nothing and turned it into something by turning it into power. The kids in the suburbs, the rich kids, have their cars, computers, designer clothing. But here comes the gang. They can be scared of us. We get a little fun out of that. It’s a way of balancing. (Ice T 2005, xviii)